Infantile BCG osteomyelitis ultimately diagnosed as a result of trauma - Katsuhiko Tabata, MD; Osamu Miyazaki, MD; Ayako Imai, MD; Reiko Okamoto, MD; Mikiko Miyasaka, MD; Yoshiyuki Tsutsumi, MD; Yoko Anami, MD; Atsuhito Seki, MD; Tatsuki Ikuse, MD, PhD; Toshinao Kawai, MD, PhD; Takashi Ishikawa, MD, PhD; Chizuko Haga, MD; et al. (Radiology Case Reports)
The BCG vaccine is effective in preventing severe tuberculosis infections in infants and young children, and it is commonly administered in Japan to those aged between 5 to 8 months. Although the incidence of adverse reactions is low, disseminated lymphadenitis and osteomyelitis have been reported as potential side effects. We encountered a case of BCG osteomyelitis with typical imaging findings. Provided the clinical presentation and imaging features are recognized, it is possible to diagnose BCG osteomyelitis definitively and exclude a number of possible differential diagnoses.